MEMBANGUN KESADARAN KEBHINEKAAN MELALUI INTEGRASI PENDIDIKAN ISLAM DAN MULTIKULTURAL DALAM PEMBELAJARAN PPKN DI KELAS 4 SD NEGERI 100801 PASAR SEMPURNA - Pasaribu, Yusti Andayati; Fata, Nahriyah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This article aims to analyze how the integration of Islamic and multicultural educational values in the learning of Pancasila and Citizenship Education (PPKn) can build awareness of diversity among 4th grade students of SD Negeri 100801 Pasar Sempurna. In the context of a pluralistic Indonesian society, efforts to instill the values of tolerance, empathy, and respect for cultural, religious, and ethnic differences are very important from an early age. The values in Islamic teachings such as justice, compassion, and universal brotherhood are in line with the principles of multiculturalism that emphasize equality and respect for diversity. The method used in this study is a literature study with a qualitative approach. The results of the study show that the integration of these values can form the character of students who are more open, tolerant, and have strong national insights. In addition, the role of teachers as value facilitators, an inclusive school environment, and curriculum support that is responsive to diversity are factors that determine the success of the implementation of diversity-oriented learning. It is hoped that this article can be a practical and theoretical reference in the development of Islamic values-based and multicultural civic education in elementary schools.